Comprehensive transcriptional atlas of human adenomyosis deciphered by the integration of single-cell RNA-sequencing and spatial transcriptomics - Chen, Tao; Xu, Yiliang; Xu, Xiaocui; Wang, Jianzhang; Qiu, Zhiruo; Yu, Yayuan; Jiang, Xiaohong; Shao, Wanqi; Bai, Dandan; Wang, Mingzhu; Mei, Shuyan; Cheng, Tao; et al. (Protein & cell, 2024)
Adenomyosis is a poorly understood gynecological disorder lacking effective treatments. Controversy persists regarding "invagination" and "metaplasia" theories. The endometrial-myometrial junction (EMJ) connects the endometrium and myometrium and is important for diagnosing and classifying adenomyosis, but its in-depth study is just beginning. Using single-cell RNA sequencing and spatial profiling, we mapped transcriptional alterations across eutopic endometrium, lesions, and EMJ. Within lesions, we identified unique epithelial ( LGR5 +) and invasive stromal ( PKIB +) subpopulations, along with WFDC1 + progenitor cells, supporting a complex interplay between "invagination" and "metaplasia" theories of pathogenesis. Further, we observed endothelial cell heterogeneity and abnormal angiogenic signaling involving vascular endothelial growth factor and angiopoietin pathways. Cell-cell communication differed markedly between ectopic and eutopic endometrium, with aberrant signaling in lesions involving pleiotrophin, TWEAK, and WNT cascades. This study reveals unique stem cell-like and invasive cell subpopulations within adenomyosis lesions identified, dysfunctional signaling, and EMJ abnormalities critical to developing precise diagnostic and therapeutic strategies.